Police Officers’ Interrogation Expertise and Major Objectives in Police Service and Training: A Comprehensive Overview of the Literature - Thielgen, Markus M.; Schade, Stefan; Niegisch, Patrick (Frontiers in Psychology, 2022)
Interrogation is a core task of practical police work. The outcomes of interrogation often provide crucial evidence for solving criminal cases. The success of interrogation depends on interactions between police officers and citizens. Based on a comprehensive literature overview, we propose a three-factor typology for interrogations by police officers. First, the competencies of police officers refer to the application of personal, professional, social, and methodological capabilities. The underlying concept of interrogation refers to the application of both explicit and implicit experience-based interrogation models. Communication refers to the goal-directed application of communication tactics and techniques. According to this typology, we discuss the major objectives of police interrogation in police service and training from police officers’ perspectives. The present study provides guidance for practical police services and training by offering an evidence-based interrogation standard.